Application Of Health Promoting University To Students' Knowledge About The Importance Of Physical Activity - Arisjulyanto, Dedy; Ikhtiar, Rian Wahyul; Akbar, Muhammad (Sean Institute, 2022)
Obesity in Indonesia occurs mostly in people aged > 18 years with the number of obesity in 2013 there were 19.66% in men and 32.90% in women, and increased in 2018 to 26.60% in men and 44,40% in women. Obesity is one of the nutritional disorders that is the biggest health challenge for the community and is the third largest cause of degenerative diseases and chronic diseases such as diabetes mellitus (DM), hypertension, cholesterol, stroke to cancer.This research was conducted at STIKES Kusuma Bangsa, Mataram City, with a sample of 82 people who were taken by total sampling technique, the data analysis used was the paired t-test with a standard significance of = 0.05. the results of data analysis showed that the number of respondents' gender was mostly female 52.4%, the distribution of the highest semester in semester 4 was 43.9%, and the distribution of the most study program was Hospital Administration study program 61%, and the results of the analysis used the paired T-test. obtained p-value 0.000 < = 0.05.There is an effect of implementing a health-promoting university on the level of student knowledge about the importance of physical activity in the STIKES Kusuma Bangsa campus. .